Pyrus pyrifolia fruit peel as sustainable source for spherical and porous network based nanocellulose synthesis via one-pot hydrolysis system - Chen, You Wei; Hasanulbasori, Muhammad Ariff; Chiat, Phang Fung; Lee, Hwei Voon (Elsevier, 2019)
In the present study, we attempted revalorization of pear (Pyrus pyrifolia L.) peel residue into high value-added nanomaterials. A green and facile one-pot isolation procedure was designed to simplify the isolation process of nanocellulose directly from pear peel residue. The one-pot approach employed in this work is interesting as the reaction involved less harmful chemicals usage and non-multiple steps. The reaction was carried out by adding hydrogen peroxide as an oxidant and chromium (III) nitrate as catalyst in the acidic medium under mild process conditions. FTIR spectroscopy proved that the pear peel derived nanocellulose was purely cellulose phases without the presence of non-cellulosic layer. XRD study indicated that the isolated nanocellulose possessed of cellulose I polymorph with high crystallinity index of 85.7%. FESEM analysis clearly revealed that the considerable size reduction during one-pot process. Remarkably, TEM analysis revealed that the isolated nanocellulose consisted of network-liked nature and spherical shaped morphologies with high aspect ratio of 24.6. TGA showed nanocellulose has lower thermal stability compared to pear peel residue. This study provided a cost-effective method and straightforward one-pot process for fabrication of nanocellulose from pear peel residue. This is the first investigation on the nanocellulose extraction from pear fruit.